4x3 la puterea 1995 - 3 la puterea 1996 -3 x 3 la puterea 1994
Răspunsuri la întrebare
Răspuns de
3
4x3la puterea 1995 - 3 la puterea 1996 - 3 x 3 la puterea 1994 =
= 4 x 3 x 3 la puterea 1994 - 3 la puterea 2 x 3 la puterea 1994 - 3 x 3 la puterea 1994 =
= 3 la puterea 1994 x ( 4 x 3 - 3 la puterea 2 - 3 ) =
= 3 la puterea 1994 x ( 12 - 9 - 3 ) =
= 3 la puterea 1994 x 0 = 0
= 4 x 3 x 3 la puterea 1994 - 3 la puterea 2 x 3 la puterea 1994 - 3 x 3 la puterea 1994 =
= 3 la puterea 1994 x ( 4 x 3 - 3 la puterea 2 - 3 ) =
= 3 la puterea 1994 x ( 12 - 9 - 3 ) =
= 3 la puterea 1994 x 0 = 0
Alte întrebări interesante
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Chimie,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă